Developing Eco-Innovative Teaching Materials through Sugarcane Husk-Based Brick Synthesis - Choiru Umatin; Aziza Anggi Maiyanti; Nur Jahan Ahmad; Yulianti Yusal; Ector Geovanny Pupiales Chuquin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
The purpose of this study is to develop brick synthesis teaching materials incorporating sugarcane husks, to be used as one of the teaching materials for the ethnoscience and edupreneurship course. The use of sugarcane husks in the brick-making process is very important to introduce to students of ethnoscience and edupreneurship courses because it provides new knowledge that can inspire scientific and economic impact. Clear and practical teaching materials are essential for the course. Therefore, this study uses the 4D model research and development method (Define, Design, Develop, and Disseminate). The technical analysis of quantitative data uses the results of the teaching material validation instrument completed by 4 expert validators, while qualitative data is obtained through a response questionnaire. Based on the study's results, the brick synthesis teaching material with the addition of sugarcane husks was deemed valid, with scores of 3.4 by learning experts, 3.2 by material physicists, and 3.3 by economists. Meanwhile, based on the results of the questionnaire distributed to 100 students, the results showed that 92% of students gave a very good response, which means that this teaching material is practical to use in learning, so it can be concluded that the brick synthesis teaching material with the addition of sugarcane husk is feasible and practical to use in learning. Keywords: teaching materials, brick synthesis, sugarcane husk